La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies

National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

L'émergence des chanteurs immigrants sur la scène de la musique populaire au Québec : l'exemple de Corneille et de Lynda Thalie - Proulx, Robert (Quebec Studies, 2008)
A l'instar des ecrivains de la litterature migrante, des chanteurs et des chanteuses venus de divers pays ont fait du Quebec leur port d'attache et le foyer de leur carriere artistique. Ce phenomene assez recent a fait qu'au cours des dix dernieres annees on a vu debarquer au Quebec des artistes d'Hai'ti, du Bresil, du Mexique, du Maroc, du Rwanda, du Tchad, de l'Algerie, et du Venezuela, chacun avec sa musique, sa couleur, et sa sensibilite propre. Dans cette nouvelle branche de la chanson quebecoise on trouve les themes de predilection de la litterature migrante tels que l'exil, la nostalgie, le sentiment de perte, l'adaptation a un nouveau pays, l'integration, le racisme, la xenophobie, et l'hospitalite. La chanson quebecoise s'enrichit de ces differents apports; car ces artistes apportent avec eux non seulement des voix, des sons et des styles musicaux nouveaux, mais aussi des themes inedits et des trames narratives originales qui refletent leur culture d'origine, leur passe, et leurs valeurs de meme que leurs emotions liees a leurs defis actueis et a leurs reves pour l'avenir. (1) Dans cet article, nous examinerons en detail l'ceuvre de deux d'entre eux: Lynda Thalie qui, selon Monique Giroux, l'experte en chanson francophone de Radio-Canada, "est, parmi les artistes neo-quebecois, celle qui a pris le plus de place et est la plus susceptible de conquerir un large public" (cite par Vignaux) et Corneille, celui qui a jusqu'a ce jour remporte le plus grand succes aussi bien commercial que d'estime. II a vendu plus d'un million et demi de ses deux premiers disques, et a lance son premier disque en anglais, "The Birth of Cornelius," au Japon en mai 2007. (2) Lynda Thalie: l'exilee d'Algerie

Global Pop On The Move: The Fame of Céline Dion Within, Outside and Across Québec - Grenier, Line (Journal of Australian Canadian Studies, 2002)

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian,; Québécois; anglophone,; francophone,; music,; newspapers,; politics,

Questions de renommée : les mises en mémoire du phénomène Céline Dion - Grenier, Line (Recherches féministes, 2000)
Dans cet article, l'auteure se penche sur le « phénomène Céline Dion » au Québec sous l'angle de la renommée. Au moyen de quelques fragments du discours qui a alimenté ce phénomène à la fin de la dernière décennie, l'auteure esquisse les contours de deux des figures concurrentes de la renommée que ce phénomène met en évidence : le « héros national » et l'« entrepreneur heureux ». Son analyse illustre comment ces figures de la renommée et les mises en mémoire auxquelles elles prêtent visibilité et valeur, lorsqu'elles sont en action dans la conjoncture québécoise contemporaine, opèrent une fusion, sinon une collusion entre la réussite individuelle et collective, entre l'intérêt personnel et national, et, par le fait même, rattachent différents ordres de matériel culturel au présent « passé » de certaines expériences privées, ressources locales et trajectoires publiques.